Modified clay minerals efficiency against chemical and biological warfare agents for civil human protection - Plachá, Daniela; Rosenbergová, Kateřina; Slabotínský, Jiří; Kutláková, Kateřina Mamulová; Studentová, Soňa; Martynková, Gražyna Simha (Journal of hazardous materials, 2014)
Sorption efficiencies of modified montmorillonite and vermiculite of their mono ionic Na and organic HDTMA and HDP forms were studied against chemical and biological warfare agents such as yperite and selected bacterial strains. Yperite interactions with modified clay minerals were observed through its capture in low-density polyethylene foil-modified clay composites by measuring yperite gas permeation with using chemical indication and gas chromatography methods. The antibacterial activities of synthetized organoclays were tested against selected Gram-positive and Gram-negative bacterial species in minimum inhibitory concentration tests. The obtained results showed a positive influence of modified clay minerals on the significant yperite breakthrough-time increase. The most effective material was the polyethylene-Na form montmorillonite, while the polyethylene-Na form vermiculite showed the lowest efficiency. With increasing organic cations loading in the interlayer space the montmorillonite efficiency decreased, and in the case of vermiculite an opposite effect was observed. Generally the modified montmorillonites were more effective than modified vermiculites. The HDP cations seem to be more effective compare to the HDTMA. The antibacterial activity tests confirmed efficiency of all organically modified clay minerals against Gram-positive bacteria. The confirmation of antibacterial activity against Y. pestis, plague bacteria, is the most interesting result of this part of the study.
Keywords: silikáty hliníku; Chemical Warfare Agents; mikrobiální testy citlivosti; biologické bojové látky; Yperite; Protective Clothing; Antibacterial activity; Polyethylene; lidé; Gram-Negative Bacteria; yperit; ochranné oděvy; chemické bojové látky; Acrylic Resins; Bentonite; akrylové pryskyřice; Mustard gas; bentonit; grampozitivní bakterie; Biological Warfare Agents; Microbial Sensitivity Tests; gramnegativní bakterie; Permeation; Aluminum Silicates; Mustard Gas; polyethylen; Gram-Positive Bacteria; Clay mineral; Humans